Comparativo de cumplimiento de normas de ecoeficiencia en las municipalidades distritales de Belén y San Juan Bautista, provincia de Maynas. 2020 - Ramirez Rojas, Rider (2022)
The general objective of this research work was to determine the degree of compliance with the eco-efficiency regulations with the administrative staff of the district municipalities of Belén and San Juan in 2020. The research, due to its approach, was quantitative, prospective, comparative descriptive level and non-experimental research design. The target population of the study consisted of two hundred administrative workers (200) from the district municipality of Belén and two hundred twenty-two (222) from the district municipality of San Juan, and a sample size equal to 33 and 35 workers who were working in the year 2020, which were present at the time of application of the data collection instrument, inclusion and exclusion criteria were taken into account, the technique used was the survey and the instrument applied was the questionnaire of twenty-two items the same which passed the tests of validity (Aiken's valid index) and reliability (Crombach's alpha test). The data obtained through the data collection instrument was analyzed taking into account the objectives and the research hypothesis and later expressed in a Basic Data Matrix (MBD) and analyzed, processed and tabulated through the statistical package Statical Product and Service Solutions (SPSS) version 25. The main results expressed that the non-compliance with the regulations on eco-efficiency in electrical energy in both municipalities is high, with values of 80.1% and 60%, in eco-efficiency in solid waste the non-compliance was of 78.8% and 80% and in paper eco-efficiency it was close to 80.8% and 100% as in the case of the district municipality of San Juan. There are significant statistical differences between the means of regulatory compliance on eco-efficiency in the energy consumption dimension between the municipalities of San Juan and Belén. There are no significant statistical differences between the means of regulatory compliance on eco-efficiency in the solid waste dimension between the municipalities of San Juan and Belén. There are significant statistical differences between the means of regulatory compliance on eco-efficiency in the paper and related dimension between both municipalities.